Intravenous Tranexamic Acid Bolus plus Infusion Is Not More Effective than a Single Bolus in Primary Hip Arthroplasty: A Randomized Controlled Trial. (September 2017) - Zufferey, Paul J.; Lanoiselée, Julien; Chapelle, Céline; Borisov, Dmitry B.; Bien, Jean-Yves; Lambert, Pierre; Philippot, Rémi; Molliex, Serge; Delavenne, Xavier; Deygas, Béatrice; Donnat, Mathilde; Techer, Juanita; et al.
Abstract : Background: Preoperative administration of the antifibrinolytic agent tranexamic acid reduces bleeding in patients undergoing hip arthroplasty. Increased fibrinolytic activity is maintained throughout the first day postoperation. The objective of the study was to determine whether additional perioperative administration of tranexamic acid would further reduce blood loss. Methods: This prospective, double-blind, parallel-arm, randomized, superiority study was conducted in 168 patients undergoing unilateral primary hip arthroplasty. Patients received a preoperative intravenous bolus of 1 g of tranexamic acid followed by a continuous infusion of either tranexamic acid 1 g (bolus-plus-infusion group) or placebo (bolus group) for 8 h. The primary outcome was calculated perioperative blood loss up to day 5. Erythrocyte transfusion was implemented according to a restrictive transfusion trigger strategy. Results: The mean perioperative blood loss was 919 ± 338 ml in the bolus-plus-infusion group (84 patients analyzed) and 888 ± 366 ml in the bolus group (83 patients analyzed); mean difference, 30 ml (95% CI, −77 to 137; P = 0.58). Within 6 weeks postsurgery, three patients in each group (3.6%) underwent erythrocyte transfusion and two patients in the bolus group experienced distal deep-vein thrombosis. A meta-analysis combining data from this study with those of five other trials showed no incremental efficacy of additional perioperative administration of tranexamic acid. Conclusions: A preoperative bolus of tranexamic acid, associated with a restrictive transfusion trigger strategy, resulted in low erythrocyte transfusion rates in patients undergoing hip arthroplasty. Supplementary perioperative administration of tranexamic acid did not achieve any further reduction in blood loss. Abstract : In a randomized, blinded trial comparing an initial bolus of tranexamic acid with an initial bolus followed by an infusion, blood loss was comparable in each group. Combining current results with five previous trials in a meta-anlaysis also shows no benefit of adding an infusion of tranexamic acid to an initial bolus.Supplemental Digital Content is available in the text.